Improving Diabetic Neuropathy Knowledge in an Urban Elderly Population: A Community-Based Intervention Study - Laurentius Johan Ardian; Aktaruddin Arief Santoso; Hilmia Fahma; Anoraga Mona Cinta Gadis Cantika Gusyono; Satria Fudi Verbimanto (UNUSA Press, 2025)
Background: The global population is aging rapidly, with older adults increasingly affected by chronic conditions such as diabetes mellitus. In Indonesia, diabetes among the elderly poses a significant public health concern, often complicated by under-recognized conditions like diabetic neuropathy. Aim: This study aimed to assess the effectiveness of a community-based intervention focused on targeted health education on diabetic neuropathy among elderly residents in urban area. Methods: A pre- and post-test design was used to assess the intervention's effectiveness. In collaboration with local health cadres and facilities, participants completed identical questionnaires on diabetic neuropathy before and after the health education session to measure improvements in knowledge. Results: A total of 143 elderly participants (median age: 65 years) were enrolled, with 73.4% being female. Post-education test scores showed a statistically significant improvement compared to pre-test scores (p<0.001p<0.001, Wilcoxon test). Of the participants, 22.4% were newly identified as having diabetes, and another 22% fell into the prediabetes range. Despite some variations in learning outcomes, 84.6% showed improved scores, indicating high effectiveness of the health education session. Conclusion: This study demonstrates that a community-based approach combining early diabetes screening and health education significantly improves elderly participants' knowledge about diabetes and diabetic neuropathy.